SOLID WASTE MANAGEMENT IN RICE PROCESSING INDUSTRIES - Saidelles, Ana Paula Fleig; Senna, Ana Júlia Teixeira; Kirchner, Rosane; Bitencourt, Gabriele (Revista Eletrônica em Gestão, Educação e Tecnologia Ambiental, 2012)
http://dx.doi.org/10.5902/223611704314 Nowadays, the environmental dimension is increasingly receiving more and moreimportance in organizations and society actions. Today, products are frequently designed,produced, marketed and consumed, taking into account the impact produced by each process inthe rice crop production chain. A major concern in this sector is with the solid waste produced bythe rice processing industry. Thus, this work aims at identifying the solid waste produced at riceprocessing agroindustry and, to come up with improvement possibilities for the destination of thissolid waste. This research was carried out at a rice processing agroindustry located at the city ofSão Sepé/RS from April to June 2010. The mapping process adopted follows a structuredobservation. Through this mapping it was possible to identify twenty and one different types ofwastes resulting from the rice processing, with ash and rice husk being the ones observed ingreater quantity. The diagnose we performed allows the industry to better know its own operationand then, propose improvements and, to perform a periodic review of the solid wastes producedduring the production process. Finally, we suggested some strategies for the waste for redirectingthe waste minimizing the environmental problems.